Pengaruh model pembelajaran Problem Based Learning (PBL) berbantuan Canva terhadap kemampuan berpikir kritis siswa sekolah dasar - Miftachul Ilma; Danang Prasetyo; Amelia Widya Hanindita (Universitas Islam Nahdlatul Ulama Jepara, 2026)
Critical thinking is an essential competency that elementary school students need to develop in science learning. However, teacher-centered instructional practices often limit students' opportunities to actively engage in critical thinking. This study aimed to examine the effect of the Problem Based Learning (PBL) model assisted by Canva on the critical thinking skills of fifth-grade students in the topic Indonesia's Biodiversity. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent control group design. The sample consisted of 50 fifth-grade students at SDN Ngagel Rejo I/396 Surabaya, divided into an experimental class and a control class, with 25 students in each group. Data were collected through an essay-based critical thinking test and analyzed using descriptive statistics, normality tests, homogeneity tests, and the Independent Samples t-test. The results showed that the experimental class achieved a higher mean posttest score (76.00) than the control class (58.60). Furthermore, the Independent Samples t-test yielded a significance value of 0.000 (< 0.05), indicating that the implementation of the Problem Based Learning model assisted by Canva had a significant positive effect on students' critical thinking skills in elementary science learning.